Myeloid Cell Mediated Immune Suppression in Pancreatic CancerSummary - Samantha B. Kemp (Elsevier, 2021)
Pancreatic ductal adenocarcinoma (PDA), the most common pancreatic cancer, is a nearly universally lethal malignancy. PDA is characterized by extensive infiltration of immunosuppressive myeloid cells, including tumor-associated macrophages and myeloid-derived suppressor cells. Myeloid cells in the tumor microenvironment inhibit cytotoxic T-cell responses promoting carcinogenesis. Immune checkpoint therapy has not been effective in PDA, most likely because of this robust immune suppression, making it critical to elucidate mechanisms behind this phenomenon. Here, we review myeloid cell infiltration and cellular crosstalk in PDA progression and highlight current therapeutic approaches to target myeloid cell-driven immune suppression.